Optimizing chickpea yield and profitability through phosphorus application and PSB inoculation in a custard apple (Annona squamosa) based agri-horti system - Makhan, S K; Dheer, A; Alok, K S; Bipin, K S; Riya, M; Sant, P; Yashpal, S (Plant Science Today, 2025)
Agroforestry offers significant environmental, economic and social benefits by integrating trees into agricultural systems. Sometimes, horticultural crops are also added, leading to agri-horti systems. This study investigates the effects of phosphorus (P) application and phosphate solubilizing bacteria (PSB) inoculation on the growth, yield and economics of Cicer arietinum L. in an Annona squamosa L. based agri-horti system. The field experiment was conducted during Rabi season of 2018–19 at the Agroforestry Research Farm, Rajiv Gandhi South Campus, Banaras Hindu University, Mirzapur, under rainfed conditions. The trial followed a factorial randomized block design (FRBD) with 12 treatment combinations, consisting of four phosphorus levels (0, 20, 40 and 60 kg P2O5/ha) and three PSB inoculation levels (0, 5 and 10 mL/kg seed), replicated thrice. The results revealed that increasing phosphorus levels and PSB inoculation significantly enhanced growth attributes such as plant height, number of branches, root nodules and dry matter accumulation. The highest yield attributes were obtained with 60 kg P2O5/ha and 10 mL PSB/kg seed inoculation. Grain yield (16.70 q/ha) and biological yield (43.25 q/ha) were maximized at 60 kg P2O5/ha, while PSB inoculation at 10 mL/kg seed resulted in a grain yield of 14.40 q/ha. Economic analysis indicated that the highest net return (₹44195) and benefit-cost ratio (2.15) were achieved with 60 kg P2O5/ha and 10 mL PSB/kg seed. These findings highlight the potential of phosphorus application and PSB inoculation in optimizing chickpea production under agroforestry systems, ensuring better resource utilization and economic returns for farmers in rainfed regions.